Gambaran Kadar Merkuri (Hg) dengan Pemberian Tanaman Eceng Gondok (Echorina crassipes) menggunakan Medode Spektrofotometer UV-Vis - Siti Zaetun; Lale Budi Kusuma Dewi; Ni Luh P. Sri Ayu Sutami D; Lalu Srigede (Poltekkes Kemenkes Semarang, 2015)
This experiment is to know the concentration of mercury (Hg) after planting eceng gondok plant (Echorina crassipes) with spectrophotometers UV-Vis method. The characteristic of this study is a true experiment with descriptive analysis and reported in the form of research table. The result shows that the mercury concentration before planting this eceng gondok is 0,0014 ppm in the level of 0,2 ppm, 0,4 ppm and in the level of 0,6 ppm. However, in the level of 0,8 ppm the mercury cocentrasion becomes 0,0012 ppm. After planting the eceng gondok for 5 days until 15 days we get the same results.